A new species of Geoplana (Platyhelminthes: Tricladida: Geoplanidae) from the Western Amazon Basin with comments on the land planarian fauna from Peru - Negrete, Lisandro; Brusa, Francisco; Damborenea, Cristina (Zootaxa, 2012)
Geoplana excelentissima sp. nov. is described from the east centre of Peru. This new species is very long (165 mm), broad andflat. The dorsal surface is black with five white stripes, and two marginal pinkish stripes with a blue inner surface. A uniquecombination of external and internal characters (e. g. the copulatory apparatus) is present in the new species. Geoplana regiaand Geoplana matuta, species known from Brazil, have some affinities with respect to the copulatory apparatus. Additionally,we provide a list of all Geoplanidae species already described for Peru with new information on the distribution of some species through the revision of the Fundación Miguel Lillo Collection (Argentina).